PELATIHAN SEHAT: CEMILAN, DAN JUS UNTUK MENINGKATKAN HEMOGLOBIN PADA SISWI SMA 59 JAKARTA - Nurul Azmah Nikmatullah; Euis Purbasari; Adia Putra Wirman; Oktadio Erikardo; Hurip Budi Riyanti; Anang Rohwiyono (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
Iron deficiency anemia is still a common health problem among teenage girls in Indonesia, including senior high school students. This condition can make students feel tired easily, have difficulty concentrating in class, and experience decreased productivity and overall quality of life. This community service program was designed to help students at SMA Negeri 59 Jakarta better understand anemia and learn practical ways to prevent it. The program focused on teaching them how to choose and prepare healthy snacks and juices made from local foods that are rich in iron and other nutrients that help the body produce hemoglobin. The activities included interactive nutrition education sessions and hands-on demonstrations on how to make simple, affordable, and nutritious snacks and juices that students can easily prepare at home. Through this program, students are expected to develop healthier eating habits. Ultimately, this initiative is hoped to become a practical promotive and preventive effort to reduce the risk of anemia among adolescent girls.